The impact of entrepreneurial team psychological capital on innovation performance: The mediating role of knowledge sharing and knowledge hiding - Chen, Minling; Mi, XueMei; Xue, Jing; Li, Yi; Shi, Junran (Frontiers in Psychology, 2023)
The important role of psychological capital on corporate innovation has attracted the attention of academics, more and more scholars have conducted related studies. Although most scholars have explored the mechanisms and paths of psychological capital on innovation performance, few scholars have explored the inner relationship between them from the perspective of knowledge management. Based on the knowledge management perspective, we explored the effects of psychological capital on knowledge sharing, knowledge hiding, and innovation performance of entrepreneurial teams in entrepreneurial contexts. We conducted hypothesis testing using data from 113 Chinese entrepreneurial teams, and conducted reliability analysis, correlation analysis, and regression analysis on the questionnaire data with the help of SPSS software and AMOS software. The results showed that (1) entrepreneurial team psychological capital has a significant positive effect on innovation performance of startups; (2) entrepreneurial team psychological capital positively promotes their knowledge sharing behavior and reduces knowledge hiding behavior; (3) entrepreneurial team knowledge sharing and knowledge hiding play a partially mediating role between entrepreneurial team psychological capital and innovation performance of startups; (4) organizational innovation climate plays a significant role in the effects of entrepreneurial team knowledge sharing (4) organizational innovation climate plays a moderating role in the influence of entrepreneurial team knowledge sharing and knowledge hiding on the innovation performance of startups. The findings are consistent with the hypothesis model proposed in this paper, indicating that as the psychological capital of entrepreneurial teams increases, the innovation performance of startups can benefit from higher levels of knowledge sharing and lower levels of knowledge hiding.